THE ROLE OF THE RESEARCH AND EDUCATION CENTER IN INNOVATION DEVELOPMENT OF A HIGHER EDUCATIONAL INSTITUTION - Alyona Yu. Levykh; Lyudmila V. Vedernikova (Высшее образование в России)
The article ascertains the role of a research and education center in providing and developing an innovation activity of a regional teachers’ training higher educational institution. The activities of this center is based on the integration and social partnership and is aimed at elaboration of the strategy of social development of the regional educational space and providing high quality of teachers’ training. The article describes the structure, main tasks of the research and education center, and the functions of the constituent laboratories.